Psychological perceptions of media channels: Effects on willingness to buy and advertisement trust - Kučinskas, Gedas (Junal Ilmu Manajemen, 2024)
This study investigated the psychological perceptions of media channels and their effects on consumer behavior, specifically focusing on willingness to buy and advertisement trust. Drawing upon theories of media effects and consumer psychology, the research examined how factors such as perceived closeness, familiarity, and identification with media channels influence consumer attitudes and behaviors. Methodologically, the study employed a mixed-methods approach, combining survey data on media usage and perceptions with experimental manipulations to assess the causal effects of psychological perceptions on consumer behavior. Findings revealed consumers' psychological perceptions of media channels, such as perceived closeness and identification, significantly impact their willingness to buy and trust in advertisements. In conclusion, this research highlights the importance of understanding the nuanced dynamics of media consumption and its implications for marketing and advertising strategies. By integrating theoretical insights with empirical findings, the study contributes to a deeper understanding of the psychological mechanisms underlying consumer behavior in the context of media channels.